Some Remarks about the Muslim Population of the Empire in the Russian Government Handbook "Alphabetical List of the Population Living in the Russian Empire" - Fayzieva Feruza (International Journal on Integrated Education, 2022)
The article aims at reviewing the national composition, number and occupation of the Muslim population of the Russian Empire on the basis of a historical document which is stored in the Turkestan Governor-General-General's Department of the National Archive of Uzbekistan.